PENGELOLAAN HOME INDUSTRY USAHA BAKPIA DI KABUPATEN KLATEN - Erlyna Wida R; Choirul Anam (Asian Journal of Innovation and Entrepreneurship, 2016)
Bakpia business development in Klaten district has not been as fast as bakpia run business entrepreneurs in Yogyakarta. The hindrance is faced by them as follow : 1) The production process is not good, 2) The process of making the dough skin and the contents are less efficient, and 3) management sub-optimal effort. This causes increased effort bakpia no significant effort. Two UKM that become partners in the program of this devotion is Jaka Santosa and UKM Harwati. Based on the problems in t the solution and approach is offered as follows: 1) Introduction of means of production is good and right, 2) introduction of appropriate technology kneading machine bakpia skin and content, and 3) Improved management.The activities carried out in both UKM partners include: 1) Introduction of means of production is good and right, 2) introduction of technology appropriate mixing machine dough skin and the contents bakpia, 3) Improved management, and 4) Facilitation of activities held at least once a month to see the development of the results that have been achieved. Results of this activity is the management of the business in both the UKM partners can increase sales volume by 25 percent. This is accomplished by saving time in the process of kneading, quality improvement and business management are increasingly significant.